Bank of England interest rate announcements and the foreign exchange market - Michael Melvin; Christian Saborowski; Michael Sager; Mark P. Taylor (Center for Economic Studies and ifo Institute (CESifo), 2009)
Since 1997, the Bank of England Monetary Policy Committee (MPC) has met monthly to set the UK policy interest rate. We examine evidence of systematic patterns in exchange rate movements on MPC days over the first decade of operation of the MPC. Daily data reveal significant differences in volatility on the last of three meeting days when the interest rate announcement surprises the market. Intraday, five-minute return data are then used to provide a microscopic view. We use a Markov-switching framework that incorporates endogenous transition probabilities, which allows for an interesting alternative characterization of macroeconomic news effects on the foreign exchange market. We find evidence for non-linear regime switching between a high-volatility, informed-trading state and a low-volatility, liquidity-trading state. MPC surprise announcements are shown significantly to affect the probability that the market enters and remains within the informed trading regime, with some limited market positioning just prior to the announcement.
Keywords: E42; E44; F31; 330; foreign exchange market; microstructure; monetary policy announcements; Markov switching; endogenous probabilities; Zinspolitik; Geldpolitik; Ankündigungseffekt; Wechselkurs; Volatilität; Devisenmarkt; Mikrostrukturanalyse; Großbritannien